Perceived learning as a mediator between institutional factors, instructor immediacy behavior, learner characteristics and course satisfaction among undergraduate distance learners - Amoozegar, Azadeh (2017)
Distance learning in Malaysia has seen phenomenal growth especially in higher education where there are numerous universities offering online courses that have specifically provided access to students who were challenged by space and time constraints. In spite of the dramatic increase of online courses and student enrollment, there are many indications that online courses are unsuccessful at meeting students’ needs and students are dissatisfied with their online course experiences, which brings about a serious concern regarding the dropout rates of online courses. For solving this issue, it is crucial that researchers identify and study the factors that lead to student satisfaction with online courses because course satisfaction is considered to be the largest determinant in reducing dropout in distance learning environment. Hence, the purpose of this study is to identify factors contributing to course satisfaction among distance learners in Malaysian research universities. The factors are categorized into institutional factors (administrative support, technology support, and university support), learner characteristics (motivation, self-regulated learning and self-efficacy) and instructor immediacy behavior. Further, investigate the role of perceived learning as a mediator, and finally, develop a model for course satisfaction in distance education setting. These factors were selected based on the social presence and transactional distance theory and on previous studies on satisfaction of students. This study is based on a quantitative descriptive design with sample size of 367 undergraduates’ students in the third-fourth years at Universiti Kebangsaan Malaysia (UKM) and Universiti Putra Malaysia (UPM). The sample was selected based on the proportional stratified technique. The main instrument used was a questionnaire, which was adopted from previous studies whose content validity was checked by panel of experts. A pilot study was conducted on 30 students to assist the reliability of the instrument, which ranged from 0.79 and 0.88 by the value of Cronbach’s alpha. The data was analyzed descriptively using IBM SPSS and inferentially using the Analysis of Moment Structure (AMOS). The descriptive findings indicated that course satisfaction level was a moderate. Among eight variables affecting course satisfaction only motivation and self-efficacy were found to be high; whereas the level of other variables including perceived learning, technical, administrative, and university support, instructor immediacy behavior and self-regulated learning were moderate. Among 22 hypotheses were tested, 20 were supported. Two hypotheses did not support in this study. The first one is the influence of technical support on perceived learning, which is rejected. Perceived learning also was not identified as mediator factor that influence technical support towards course satisfaction. The most salient factor influencing course satisfaction was instructor immediacy behavior (β= 0.236, P< 0.01), followed by administrative support (β= 0.198, P< 0.001), university support (β= 0.229, P< 0.001), and self-efficacy (β= 0.179, P= 0.01). Contrary, technical support (β= 0.11, P= 0.039) and self-regulated learning (β= 0.11, P= 0.034) perceived as less important factor influencing course satisfaction among distance learning students in Malaysian Research Universities. The findings of this study concurred that the influence of administrative support (β= 0.06, P= 0.007), university support (β= 0.049, P=0.013) and instructor immediacy behavior (β= 0.094, P=0.001) partially mediated by perceived learning, whereas the influence of motivation (β= 0.058, P= 0.021), self-regulated learning (β= 0.042, P= 0.038), and self-efficacy (β= 0.076, P= 0.003) fully mediated by perceived learning. The results attained from the analyses also produced a model that predicts the satisfaction of students among the undergraduates, which explained 69.7% of course satisfaction. Several implications were also drawn from the findings of this study. The proposed model is a definitive model that synthesizes what is known and provides knowledge to guide future research in related field.